Ruthadele Sarter and Mrs. Sargent (Lucille) Wright - Unknown:::Creator::::::::::::
Photograph shows from left to right Ruthadele Sarter and Mrs. Sargent (Lucille) Wright holding a large white sign with the YWCA insignia.